2017
DOI: 10.1136/openhrt-2017-000620
|View full text |Cite
|
Sign up to set email alerts
|

The impact of passive and active smoking on inflammation, lipid profile and the risk of myocardial infarction

Abstract: ObjectiveTo investigate the effect of passive smoking, active smoking and smoking cessation on inflammation, lipid profile and the risk of myocardial infarction (MI).MethodsA total of 423 cases with a first MI and 465 population controls from the Maltese Acute Myocardial Infarction (MAMI) Study were analysed. Data were collected through an interviewer-led questionnaire, and morning fasting blood samples were obtained. ORs adjusted for the conventional risk factors of MI (aORs) were calculated as an estimate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 25 publications
1
36
1
2
Order By: Relevance
“…In a study conducted by Attard et al, it was reported that exposure to PS increased the risk of MI (OR 3.2 [95% CI 1.7, 6.3]), with the OR being higher for individuals exposed to PS at home rather than in a public setting (OR 2.0 [95% CI 0.7, 5.6] vs. OR 1.2 [95% CI 0.7, 2.0]) . Likewise, we found increased risk of CVD in subjects who were exposed to PS in the workplace and at home.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In a study conducted by Attard et al, it was reported that exposure to PS increased the risk of MI (OR 3.2 [95% CI 1.7, 6.3]), with the OR being higher for individuals exposed to PS at home rather than in a public setting (OR 2.0 [95% CI 0.7, 5.6] vs. OR 1.2 [95% CI 0.7, 2.0]) . Likewise, we found increased risk of CVD in subjects who were exposed to PS in the workplace and at home.…”
Section: Discussionsupporting
confidence: 74%
“…It has also been evidenced that PS could increase the risk of coronary heart disease by 70–80% . Furthermore, meta‐analytic evidence highlighted the association between PS and a minor increase in the risk of coronary heart disease, while this finding was not obtained in another case–control study …”
Section: Introductionmentioning
confidence: 97%
“…42 Even one cigarette per day may increase the risk for CAD and stroke, which is much more pronounced among individuals who smoke ≥20 cigarettes per day. 42 Also exposure to environment/secondhand cigarette smoke may increase the risk for incident CAD and deaths from CAD, [43][44][45] supporting the notion that smoking has a harmful effect on general health and survival outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, it seems a bit unexpected that unprocessed red meat does not increase CRP and triglycerides or decrease HDL cholesterol in current smokers; however, it is not surprising that unprocessed red meat may make modest contributions to inflammation and disturbed lipid levels when compared to cigarette smoking in current smokers. Cigarette smoking can significantly increase circulating inflammation and triglycerides and reduce HDL cholesterol …”
Section: Discussionmentioning
confidence: 99%
“…One important modifier is smoking. Smoking can lead to oxidative stress, inflammation, abnormal blood lipid levels, metabolic syndrome, cardiovascular disease and many chronic diseases . Quitting smoking cannot remove the damage caused by smoking in the past; therefore, past smokers are more susceptible to exogenous insults, such as factors that can initiate inflammation or disturb lipid levels, than never smokers.…”
Section: Introductionmentioning
confidence: 99%